Pediatric burns research: A history or an evolution?. Issue 7 (November 2015) - McDowell, Dermot T.; Hyland, Ela J.; Harvey, John G.; Holland, Andrew J.A.
Highlights Pediatric burns research has become a subspecialty in its own right. There are no dedicated pediatric burns journals. Historically, pediatric burns research was published in a wide variety of journals. Significantly more pediatric burns research has been published in recent years. Two burns journals have consolidated 37% of the published pediatric burns research.